Riegl, Strzygowski and the development of art - Georg Vasold (Journal of Art Historiography, 2011)
Originally published in Towards a Science of Art History: J. J. Tikkanen and Art Historical Scholarship in Europe, Helsinki: Society of Art History, 2009.The lifelong rivalry between Alois Riegl and Josef Strzygowski, both prominent members of the Vienna School, not only had personal, but mainly methodological and ideological reasons. Born and raised up in the very eastern parts of the Hapsburg monarchy, both Riegl and Strzygowski were strongly interested in the status of art beyond the academic canon. Their research on widely ignored subjects like folk art, baroque, and late antiquity, clearly reflect the shared intention to enlarge the field of art history writing. In doing so, however, they came to complete different results. Whereas for Strzygowski art history must be seen as a permanent struggle between a dominant powerful art (“Machtkunst”) and diverse suppressed artistic ideas, Riegl emphasized the concept of mixing cultures. For him art was always the result of different, antagonistic and dissident artistic streams. This idea of a transforming art – art that is in a constant flux, always creating new forms and values – was rigidly fought by Strzygowski. For the latter, whose anti-Semitic writings reflect an irrational fear of hybrid cultural forms, art only gains a certain cultural value when it is ‘pure’, untouched by external influences.